PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DENGAN MENGGUNAKAN METODE EKSPERIMEN DI SDN 32 PANINJAUAN - Susanti, Weli (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research intent to describe result step-up studies IPA by use of experiment method at brazes IV SDN 32 Paninjauan. This observational result point out step-up on RPP of I. cycle 75% worked up as 90,62% on cycle II. On activity learns I. cycle 76,78% worked up as 91,06% on cycle II. Student activity on I. cycle of 74,99% worked up as 91,08% on cycle II. Meanwhile studying result of kognitif's aspect I. cycle 69,67 worked up on silus II. 83,82. On afektif's aspect I. cycle 75,35 worked up on cycle II. 84,26. Then psikomotor's aspect of I. cycle 71,88 worked up on cycle II. 83,93. Kata Kunci: Hasil belajar, IPA, metode, eksperimen.